Finding space to mental health : promoting mental health in adolescents (12 to 14 year olds): preliminary results of the intervention's effectiveness - Campos, Luísa (2015)
Mental health and well-being are fundamental to our collective and individual ability as humans to think, to feel emotions, to form and maintain relationships, to study, to pursue leisure interests, to make day-to-day decisions and to enjoy a fulfilling life. A healthy adolescence is a prerequisite for a healthy adulthood. However, the current reality presents a concerning picture. The formation of individual and collective mental capital – especially in the earlier stages of life – is being held back by a range of avoidable risks to mental health (World Health Organization [WHO], 2013). Adolescents from Southern Europe (region that has been more severely hit by the financial crisis; e.g., Portugal) are pointed out as an extremely vulnerable group, as their mental health might easily be influenced by their parents’ economic difficulties and by the lack of social solidarity (European Parliament, 2012). Adolescents’ mental health promotion is regarded as a vital concern (WHO, 2005a, 2013). Interventions focused on mental health literacy promotion have revealed important advantages in preventing, recognising, early intervening and reducing stigma (Pinfold, Stuart, Thornicroft & Arboleda-Florez, 2005; Pinfold, Toulmin, Thornicroft, Huxley, Farmer & Graham, 2003; Schulze, Richter-Werling, Matschinger & Angermeyer, 2003; Stuart, 2006). Consistent with mental health promotion frameworks proffered by the World Health Organization (2005a), we must engage with young people in environments where they interact (Burns, 2011). Schools are implicitly one of the most important settings for promoting the mental health of adolescents (Barry, Clarke, Jenkins & Patel, 2013; WHO, 2001). The “Finding Space to Mental Health: Promoting mental health in adolescents (12- to 14 year olds)” project aims at increasing young people’s mental health literacy. During the first year, an assessment instrument – Mental Health Literacy questionnaire (MHLq) - and a two-day intervention were developed. The intervention is composed by 2 sessions at one-week intervals, lasting 90 minutes each. Sessions follow an interactive methodology, using group dynamics, music and videos and group discussions regarding participants’ emotional well-being. The study of the intervention’s effectiveness is conducted through a pretest-postest design using the MHLq in both an experimental group and a control group. This article presents the preliminary results regarding the effectiveness of the intervention aimed at enhancing mental health literacy in a sample of 100 Portuguese adolescents (12- to 14-year-olds). The postest showed students’ increased levels of knowledge and self-help strategies. These results suggest that the intervention developed appears to be adequate to the proposed goal, and they strengthen the belief that targeting young people in systematic and sustainable school-based intervention is a promising approach for the promotion of mental health literacy (Rickwood, Deane, Wilson & Ciarrichi, 2005; Schulze et al., 2003; WHO, 2010).